EXAMING CURRENT PROVISION, PRACTICE AND EXPERIENCE OF INITIAL TEACHER TRAINING PROVIDERS IN IRELAND PREPARING PRE SERVICE TEACHERS FOR THE INCLUSION OF STUDENTS WITH SPECIAL EDUCATION NEEDS IN PHYSICAL EDUCATION CLASSES - Crawford, Susan; O'Reilly, R.; Flanagan, N. (European Journal of Adapted Physical Activity, 2012)
Research from an international perspective in relation to the preparation of pre service teachers in physical education and special educational needs indicates that initial teacher training providers are inconsistent in the amount of time spent addressing the issue and the nature of curricular content (Vickerman, 2007). In Ireland, research of Meegan and MacPhail (2005) and Crawford (2011) indicates that physical education teachers do not feel adequately prepared to accommodate students with Special Educational Needs (SEN) in physical education classes. This study examined initial teacher training provision in Ireland in the training of pre service physical education teachers in SEN. The methodology used was qualitative and included questionnaires and interviews (n=4). Findings indicated that time allocation (semester long modules), working with children with disabilities in mainstream settings (school or leisure centre based), lack of collaboration with other PETE providers (n=4) and a need for continued professional development were themes in need of address. Using a combined approach where the recently designed European Inclusive Physical Education Training (Kudlácěk, Jesina, & Flanagan, 2010) model is infused through the undergraduate degree programme is proposed. Further, the accommodation of hands on experience for undergraduates in mainstream settings and the establishment of inter institutional communities of practice, with a national disability research initiative, is essential to ensure quality adapted physical activity training can be accommodated throughout Ireland.
Keywords: Initial teacher training; physical education; Special Educational Needs; Inclusion